5-(4,6-Dimorpholino-1,3,5-triazin-2-yl)-4-(trifluoromethyl)pyridin-2-amine (PQR309), a Potent, Brain-Penetrant, Orally Bioavailable, Pan-Class I PI3K/mTOR Inhibitor as Clinical Candidate in Oncology - Beaufils, Florent (J Med Chem, 2017)
Phosphoinositide 3-kinase (PI3K) is deregulated in a wide variety of human tumors and triggers activation of protein kinase B (PKB/Akt) and mammalian target of rapamycin (mTOR). Here we describe the preclinical characterization of compound 1 (PQR309, bimiralisib), a potent 4,6-dimorpholino-1,3,5-triazine-based pan-class I PI3K inhibitor, which targets mTOR kinase in a balanced fashion at higher concentrations. No off-target interactions were detected for 1 in a wide panel of protein kinase, enzyme, and receptor ligand assays. Moreover, 1 did not bind tubulin, which was observed for the structurally related 4 (BKM120, buparlisib). Compound 1 is orally available, crosses the blood−brain barrier, and displayed favorable pharmacokinetic parameters in mice, rats, and dogs. Compound 1 demonstrated efficiency in inhibiting proliferation in tumor cell lines and a rat xenograft model. This, together with the compound’s safety profile, identifies 1 as a clinical candidate with a broad application range in oncology, including treatment of brain tumors or CNS metastasis. Compound 1 is currently in phase II clinical trials for advanced solid tumors and refractory lymphoma.